Cytophagic histiocytic panniculitis, hemophagocytic lymphohistiocytosis and undetermined autoimmune disorder: reconciling the puzzle - Pasqualini, Claudia (BioMed Central, 2014)
Cytophagic histiocytic panniculitis is a rare disease, associated with either nonmalignant conditions or subcutaneous panniculitis-like T-cell lymphoma, and often also associated with hemophagocytic lymphohistiocytosis (HLH). We report the case of a 11-year-old boy with a history of secondary HLH who, after a local trauma, developed a painful, indurated plaque over the right thigh associated with relapsing HLH. Histopathologic findings from skin biopsy specimens revealed significant lobular panniculitis with benign histiocytes showing hemophagocytosis. High-dose intravenous methylprednisolone and cyclosporine A treatment was highly effective. A genetic study after a new, relapsing episode of HLH revealed an heterozygous missense mutation on STX 11 gene inherited from the mother.